Pregnant Bodies in Social Context: Natural, Disruptive, and Unrecognized Pregnancy. Issue 3 (28th June 2013) - Neiterman, Elena
<x xml:space="preserve">Abstract</x> This article examines the role of social context in the construction of meanings attached to the pregnant body. Analyzing interviews with 42 women who, during the time of the interview, were either pregnant or had given birth to a child within the last 12 months, I explore (1) the role of social context in assigning social value to the pregnant body; and (2) how the meaning attached to pregnancy changes as pregnant women move from one social context to another. I suggest that the role of social context is central to our understanding of how pregnant women are perceived and evaluated by others.